FROM VULCANIAN EXPLOSIONS TO SUSTAINED EXPLOSIVE ERUPTIONS: THE ROLE OF DIFFUSIVE MASS TRANSFER IN CONDUIT FLOW DYNAMICS - Mason R.M.; Starostin A.B.; Melnik O.E.; Sparks R.S.J. (My University, 2006)
Magmatic explosive eruptions are influenced by mass transfer processes of gas diffusion into bubbles caused by decompression. Melnik and Sparks [Melnik, O.E., Sparks, R.S.J. 2002, Modelling of conduit flow dynamic during explosive activity at Soufriere Hills Volcano, Montserrat. In: Druitt, T.H., Kokelaar, B.P. (eds). The Eruption of Soufriere Hills Volcano, Montserrat, from 1995 to 1999. Geological Society, London, Memoirs, 21, 307-317] proposed two end member cases corresponding to complete equilibrium and complete disequilibrium. In the first case, diffusion is fast enough to maintain the system near equilibrium and a long-lived explosive eruption develops. In the latter case, pre-existing bubbles expand under conditions of explosive eruption and decompression, but diffusive gas transfer is negligible. This leads to a much shorter eruption. Here we develop this model to consider the role of mass transfer by investigating transient flows at the start of an explosive eruption triggered by a sudden decompression. The simulations reveal a spectrum of behaviours from sustained to short-lived highly non-equilibrium Vulcanian-style explosions lasting a few tens of seconds, through longer lasting eruptions that can be sustained for tens of minutes and finally to eruptions that can last hours or even days. Behaviour is controlled by a mass-transfer parameter, ω, which equals n*2/3D, where n* is the bubble number density and D is the diffusivity. The parameter ω is expected to vary between 10- 5 and 1 s- 1 in nature and reflects a time-scale for efficient diffusion. The spectrum of model behaviours is consistent with variations in styles of explosive eruptions of silicic volcanoes. In the initial stages peak discharges occur over 10-20 s and then decline to low discharges. If a critical bubble overpressure is assumed to be the criterion for fragmentation then fragmentation may stop and start several times in the declining period causing several pulses of high-intensity discharge. For the cases of strong disequilibria, the fluxes can decrease to negligible values where other processes, such as gas escape through permeable magma, prevents explosive conditions becoming re-established so that explosive activity stops and dome growth can start. For cases closer to the equilibrium the eruption can evolve towards a quasi-steady sustained flow, never declining sufficiently for gas escape to become dominant. © 2005 Elsevier B.V. All rights reserved.
Keywords: DIFFUSION; EXPLOSIVE ERUPTION; EXTRUSION; FRAGMENTATION